LIMITS OF DEMOCRATIC CONSOLIDATION. UNDERMINING REASON AS A POST-TOTALITARIAN SYNDROME. - Petrescu, Dragoş (Porównania, 2019)
My intervention on Aviezer Tucker’s book addresses four key issues, which Francis Fukuyama defines as the four levels on which consolidation of democracy must take place: (1) ideology; (2) institutions; (3) civil society; and (4) culture. Tucker’s analysis provides insightful reflexions on the role played by each of these four spheres in the post-totalitarian setting. By thoroughly examining totalitarian legacies, Tucker concludes that totalitarianism is not dead and has already made a partial return. To resist and even reverse this phenomenon, he sets forth a disarmingly simple solution: the return of dissidents. Neo-dissidents might save their post-totalitarian societies from hate, lies and sheer pragmatism through love, truth and personal integrity. Only time will tell if Tucker’s solution works.